ASS234, As a New Multi-Target Directed Propargylamine for Alzheimer's Disease Therapy - Marco-Contelles, José; Unzeta, Mercedes; Bolea, Irene; Esteban, Gerard; Ramsay, Rona R.; Romero, Alejandro; Martínez-Murillo, Ricard; Carreiras, M. Carmo; Ismaili, Lhassane (Frontiers in Neuroscience, 2016)
The complex nature of Alzheimer’s disease (AD) has prompted the design of Multi-Target-Directed Ligands (MTDL) able to bind to diverse biochemical targets involved in the progress and development of the disease. In this context, we have designed a number of MTD propargylamines showing antioxidant, anti-beta-amyloid, anti-inflammatory, as well as cholinesterase and monoamine oxidase inhibition capacities. Here, we describe these properties in the MTDL ASS234, our lead-compound ready to enter in pre-clinical studies for AD, as a new multipotent, permeable cholinesterase/monoamine oxidase inhibitor, able to inhibit Aβ-aggregation, possessing antioxidant and neuroprotective properties.